Strategies for achieving sustainable competitive advantage through innovative management accounting in manufacturing - LAOSIRIRAT, ADISAK; CHANKAEW, KEATTISAK (International Journal of Multidisciplinary Research and Studies, 2024)
The objectives of this research article were 1) to study the management accounting innovations in the manufacturing industry business. 2) to study the sustainable competitive advantage of the manufacturing industry business and 3) to study the relationship of the management accounting innovations with competitive advantage of the manufacturing industry business. The sample group used in this research were 385 business in manufacturing industry in the eastern region. The research tool was a questionnaire. The statistics used to analyze is correlation analysis and multiple regression analysis. The results revealed that management accounting innovation (strategic cost management, management quality control and strategic analysis system) have a significant positive association with sustainable competitive advantage (cost leadership and differentiation). On the other hand, integration performance measurement has no influence on sustainable competitive advantage, management quality control has no influence on differentiation. Theoretical and professional contributions, conclusion and directions for future research were highlighted.